Calycosin inhibits hepatocyte apoptosis in acute liver failure by suppressing the TLR4/NF‐κB pathway: An in vitro study - Le Chang; Aiqing Zhang; Wenjuan Liu; Ping Cao; Lixian Dong; Xiaoxue Gao (Immunity, Inflammation and Disease, 2023)
Abstract Background Acute liver failure (ALF) is a serious liver disease that is difficult to treat owing to its unclear pathogenesis. This study aimed to investigate the roles and molecular mechanisms of calycosin (CA) in ALF. Methods In this study, the roles and mechanism of CA in ALF were explored using an in vitro lipopolysaccharide (LPS)‐induced ALF cell model. Additionally, 3‐(4,5‐dimethyl‐2‐thiazolyl)−2,5‐diphenyltetrazolium bromide assay was used to assess the effect of CA on the activity of LPS‐induced L02 human liver epithelial cells, and flow cytometry was used to detect apoptosis in L02 cells. Expression levels of apoptosis‐related genes, Bax and Bcl‐2, were measured using reverse transcription‐quantitative polymerase chain reaction and Western blot analysis. Expression levels of inflammatory factors in LPS‐induced L02 cells were measured using an enzyme‐linked immunosorbent assay. Additionally, the effect of CA on ALF was inhibited via transfection of a toll‐like receptor 4 (TLR4)‐plasmid to elucidate the relationship between CA and TLR4/nuclear factor (NF)‐κB signaling pathway in ALF. Results CA had no toxic effects on L02 cells, but enhanced the activity of LPS‐induced L02 cells in a dose‐dependent manner. Apoptosis and inflammatory factor release was increased in ALF, activating the TLR4/NF‐κB signaling pathway. However, CA treatment inhibited the apoptosis and release of inflammatory factors. Further mechanistic studies revealed that the upregulation of TLR4 expression reversed the alleviating effects of CA on inflammation and apoptosis in LPS‐induced L02 cells. Conclusion CA alleviates inflammatory damage in LPS‐induced L02 cells by inhibiting the TLR4/NF‐κB pathway and may be a promising therapeutic agent for ALF treatment.